Performance and Meaning in Wedding Pantun: An Ethnopoetic Perspective - Tika Okta Sari; Liza Andriani; Vebi Andra; Muhammad Sufian (Yayasan Darussalam Bengkulu, 2023)
This study investigates the forms and meanings of pantun performed during wedding ceremonies in the Pasemah community of Padang Guci Hulu, Kaur Regency, Bengkulu, Indonesia. Using a qualitative field-research design, data were collected through participant observation, documentation of speech events, and semi-structured interviews with pantun performers and witnesses. A corpus of thirty-three pantun was compiled, transcribed, and analyzed thematically to identify typologies of form and domains of meaning. Findings reveal six major pantun categories advice, religious, humorous, love, affection, and karmina each fulfilling distinct yet complementary ritual functions. Advisory pantun transmit moral norms such as filial piety, patience, and gratitude; religious pantun ground household life in Islamic values; humorous pantun regulate collective emotions; love pantun normalize expressions of affection within ritual decorum; affection pantun emphasize empathy and social responsibility; and karmina pantun provide concise rhetorical closure. Across these forms, five dominant semantic domains emerge: family, religion, destiny (jodoh), communal life, and tolerance. Poetic conventions such as the sampiran–isi structure, ab–ab rhyme, parallelism, and local imagery of ecology and livelihood root pantun firmly in the Pasemah cultural landscape. Functioning simultaneously as entertainment, education, social control, and religious transmission, pantun serve as a multidimensional cultural instrument that affirms identity and cohesion within one of the community’s most consequential life-cycle rites. Theoretically, this study contributes to ethnopoetic scholarship by linking text and performance, while practically offering authentic resources for cultural preservation and education. Limitations include the modest corpus size and lack of multimodal documentation; future research should expand across ceremonies and communities to map archipelagic variation.